If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3x + -35 = 11 Reorder the terms: -35 + 5x + -3x = 11 Combine like terms: 5x + -3x = 2x -35 + 2x = 11 Solving -35 + 2x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 2x = 11 + 35 Combine like terms: -35 + 35 = 0 0 + 2x = 11 + 35 2x = 11 + 35 Combine like terms: 11 + 35 = 46 2x = 46 Divide each side by '2'. x = 23 Simplifying x = 23
| -2(x-5)+2=12 | | 7x-3=6x+7x+6 | | 10(5c-1)-10=48c+10 | | 6(6x+14)=480 | | -5m-10=2-(m+4) | | 124=x+165 | | 11x+x^2+20=0 | | 9(5x-11)=216 | | -6*-6.5=x | | 30+3m=117 | | y=9-14x-5 | | 4(-2-3x)=-9x-4 | | 6x-4x+10=40-2x | | 3xy+x=240 | | -6*-6.5= | | -4(x+5)+3=6(x+2)+9 | | -6x-3=-4x+1 | | 5(y+x)=20+3y | | 4x+25=60 | | (-8.2)+(-3.3)= | | f(x)=10x-7 | | -4w-11=4w+21 | | 16+3n+n=52 | | x-3(9)=-4 | | x+3=1.5 | | f(x)-2x+5whenf(x)=75 | | 1.4+1.1=8.3-m | | 5=49-7 | | 4y-3y-4=5 | | -2y-0.1-0.9y-4.6y-5= | | 7x+1=51+2x | | 4y-x=5 |